IIUM tracer study 2014: follow up - Rokis, Rohaiza; Abd Rahman, Saodah; Zubairi, Ainol Madziah; Dzulkifli, Mariam Adawiah; Md Ghalib, Mohd. Feham; Abdul Rahman, Shukran; Saidin, Aznan Zuhid; Zul Kepli, Mohd Yazid; Tunku Mohd Mokhtar, Tunku Mohar; Wan Husain, Wan Rohaida (Alumni and Career Service Division, 2015)
IIUM Tracer Study 2014 Follow-Up (IIUMTS2014FU) is a pioneering research project that has been initiated by the Ministry of Education, Malaysia (MOE). The objective of the research is to update the employment status of the university graduates in Malaysia. The sample is the graduates in 2014. The data was collected 6-months after their graduation. The sampling involved a random selection by MOE. The nature of the inquiry was the follow-up questions on the employment status of the graduates from all universities in Malaysia. The methodology was to conduct telephone interview to the sample based on the name list provided by MOE. The research managed to collect a total of 300 graduates via phone interview and online survey.